1999
DOI: 10.1238/physica.regular.060a00584
|View full text |Cite
|
Sign up to set email alerts
|

The Optical Absorption Edge of p-Type Tl(1-x)GaPrxSe2and TlGaSe2

Abstract: p-TlGaSe 2 and Tl (1-x) , GaPr x Se 2 single crystals were grown by the modi¢ed Bridgman-Stockbarger method. The absorption measurements were carried out in p-TlGaSe 2 and TI (1-x) GaPr x Se 2 samples in temperature range 10^320 K with a step of 10 K. The phonon energies calculated for p-TlGaSe 2 , p-TI 0.999 GaPr 0.001 Se 2 and p-Tl 0.995 GaPr 0.005 Se 2 are 34.0 meV, 30.0 meV and 35.0 meV, respectively. At 300 K, the direct band gaps of p-TlGaSe 2 , p-Tl 0.999 GaPr 0.001 Se 2 and p-Tl 0.995 GaPr 0.005 Se 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
4
6
0
Order By: Relevance
“…In conclusion, our results agree with those of the literature [5,9,17,[23][24][25][26][27][28][29]. TlGaSe 2 and TlGaSe 2 : Gd single crystals were grown by the Stockbarger method.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In conclusion, our results agree with those of the literature [5,9,17,[23][24][25][26][27][28][29]. TlGaSe 2 and TlGaSe 2 : Gd single crystals were grown by the Stockbarger method.…”
Section: Resultssupporting
confidence: 92%
“…The temperature coefficients (δ) of the direct band gap were calculated to be 5.185 × 10 −4 eV K −1 for both samples by fitting the experimental curves using equation (6). A reasonably good agreement was obtained with results of [23,24]. Also, for TlGaSe 2 and TlGaSe 2 : Gd samples β were calculated to be 185 K. For indirect band gap, the temperature coefficient was calculated by using the same method, to be 3.599 × 10 −4 eV K −1 , and β was found to be 205 K for TlGaSe 2 sample.…”
Section: Resultssupporting
confidence: 55%
“…The direct energy gap and the width of the tail of TlInS 2 layered single crystal are listed in Table (2). These results are in agreement with literature reports [6,22,24].…”
Section: Optical Propertiessupporting
confidence: 94%
“…The experiments were carried out under nitrogen atmosphere. While the sample was heated from ∼80 to ∼300 K using a heating rate of 1 K min 1 controlled by temperature controller (Lake Shore Model 336), the pulses were recorded by PXI 5124 High Resolution Digitizer. By employing the method of pulse-echo overlap, ultrasonic sound velocity was calculated versus temperature.…”
Section: Crystal Characterization 221 Ultrasonic Measurementsmentioning
confidence: 99%
“…TlGaSe 2 is a typical ternary A B C III III VI 2 dichalcogenide belonging to the family of van der Waals bonded layered semiconductors in a bulk phase. TlGaSe 2 is a p -type semiconductor having a high optical transmission (∼70%) at the UV -visible wavelengths and a direct energy band gap ranging between about E g ∼ 2.0 and ∼2.23 eV [1][2][3][4]. Some researchers have reported that TlGaSe 2 is a typical indirect band gap semiconductor with a band gap varying from ∼1.83 to ∼2.13 eV [5][6][7][8] at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%